Analisis Risiko Makanan Halal Di Restoran Menggunakan Metode Failure Mode and Effect Analysis - Wildatus Sholichah; Iwan Vanany; Adi Soeprijanto; Moch. Khoirul Anwar; Lilik Fatmawati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
The halal food served in restaurants is important for Muslim consumers and it is one of the most susceptible issues for restaurant business. Therefore, restaurant internal efforts to ensure the halal food by examining critical risks including the way to manage them become important to be execute by restaurant management. This research aims to create a model using Failure Mode and Effect Analysis (FMEA) method to identify and analyze the existing risks. Moreover, it also explains some improvement programs toward the risk management. The results of the risk identification and analysis will be determined by using Risk Priority Number (RPN). It is categorized that 7% risk event is classified as ‘very high risk’, 50% as ‘high risk’, 25% as ‘moderate risk’, and 18% considered as ‘low risk’. Furthermore, the improvement programs explained in this research are about delivery order system, packaging improvement, and also training, reward and punishment system. These programs are mainly purposed to reduce the risk with ‘high risk’ category.